1995
DOI: 10.1155/1997/195689
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Algebra Framework for Static High Performance Fortran Code Distribution

Abstract: High Performance Fortran (HPF) was developed to support data parallel programming for single-instruction multiple-data (SIMD) and multiple-instruction multiple-data (MIMD) machines with distributed memory. The programmer is provided a familiar uniform logical address space and specifies the data distribution by directives. The compiler then exploits these directives to allocate arrays in the local memories, to assign computations to elementary processors, and to migrate data between processors when required. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 31 publications
0
47
0
1
Order By: Relevance
“…The automatic transformation process in Par4All is heavily based on pips compiler framework phases [17,1]. The latter uses a linear algebra library [2] to analyze, transform and parallelize programs using polyhedral representations [11]. Parallel loop nests are outlined (i.e.…”
Section: Fully Automatic Approach: Par4allmentioning
confidence: 99%
“…The automatic transformation process in Par4All is heavily based on pips compiler framework phases [17,1]. The latter uses a linear algebra library [2] to analyze, transform and parallelize programs using polyhedral representations [11]. Parallel loop nests are outlined (i.e.…”
Section: Fully Automatic Approach: Par4allmentioning
confidence: 99%
“…Le processus de transformation automatisée dans PAR4ALL repose fortement sur les capacités des passes de PIPS. Ce dernier utilise une librairie d'algèbre linéaire [1] pour manipuler une représenta-tion polyédrique des abstractions d'un programme [8] et détecter les nids de boucles parallèles. Ces boucles sont ensuite extraites dans des fonctions marquées exécutables sur le GPU, ce qu'on appelle des noyaux dans la terminologie de programmation hybride.…”
Section: Approche Entièrement Automatisée : Par4allunclassified
“…In addition, the arrays are assumed to have the most general data alignments and data distributions. Ancourt et al have shown in [2] how systems of inequalities could be used to conveniently express alignment and distribution information, in addition to synthesizing distributed code for loops qualified by the INDEPENDENT directive. We have applied their representations in our framework, extending the scheme to handle general DO loops.…”
Section: Contributionsmentioning
confidence: 99%
“…Consider the following code excerpt in HPF: t =ĈP c +Ĉ p +l (2) c =0 (3) wherẽ lA ã ũA (4) 0 t ũT ,l T (5) 0 p P1 (6) 0 l Ĉ1 (7) For the given example, the corresponding matrices and vectors are: The solution set forã in the above system directly gives us the ownership set, which is a function of the processor identity vectorp, amongst other parameters such as the template cell vectort.…”
Section: An Overview Of the Linear Algebra Frameworkmentioning
confidence: 99%